Inconsistency in Ethics - Hämäläinen, Nora Fiona Karolina (Cambridge University Press, 2020)
Consistency is usually seen as one of the hallmarks and a cardinal virtue of moral theory, as well as of any defensible real-life moral perspective. In everyday life a consistent set of moral beliefs is conductive to moral clarity, communicability, responsibility and responsiveness. But this is just one side of the story. In this paper I argue that inconsistency, properly understood, is a productive and constructive aspect of both moral philosophy and our moral lives. After an introductory glance at Ralf Waldo Emerson and Hannah Arendt, the argument proceeds in three main steps. First, I discuss the philosophical importance of paying heed to inconsistencies in our moral lives, which often are prematurely pruned from moral philosophy. Second, I discuss the positive moral roles of inconsistency in terms of responsiveness to different situations, values, needs and concerns that call upon our attention in everyday life. Third, I argue that moral inconsistencies contribute to the necessary adaptability of our moral understandings to changing conditions. Fourth, in the place of a conclusion, I revisit the issue of consistency, clarity and accountability.
Keywords: consistency; inconsistency; ethics